2024
DOI: 10.26599/fshw.2022.9250081
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based meat analogues aggravated lipid accumulation by regulating lipid metabolism homeostasis in mice

Abstract: To determine the effects of plant-based meat analogues on the metabolic health and the possible mechanisms, mice were fed with a real pork diet (AP), a real beef diet (AB), a plant-based pork analogue diet (PP) and plant-based beef analogue diet (PB) for 68 days. Compared with real meat, the plant-based meat analogues increased food and energy intake, body weight, white fat and liver weight and caused adipocyte hypertrophy, hepatic lipid droplet accumulation, and more severe inflammatory responses in mice. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…253 An in vivo animal (mice) feeding study reported that consumption of plant-based meat analogs promoted an increase in body weight, lipid deposition, and inflammation relative to consumption of real beef or pork, which was attributed to upregulation of specific genes. 254 Another animal study suggested that consumption of plant-based meat analogs promoted increased food consumption compared to real meat by increasing the levels of appetite-stimulating factors, 255 which could lead to overeating and obesity.…”
Section: Alternative Protein Sourcesmentioning
confidence: 99%
“…253 An in vivo animal (mice) feeding study reported that consumption of plant-based meat analogs promoted an increase in body weight, lipid deposition, and inflammation relative to consumption of real beef or pork, which was attributed to upregulation of specific genes. 254 Another animal study suggested that consumption of plant-based meat analogs promoted increased food consumption compared to real meat by increasing the levels of appetite-stimulating factors, 255 which could lead to overeating and obesity.…”
Section: Alternative Protein Sourcesmentioning
confidence: 99%